Factors affecting conviction rates of intoxicated driver patients in two large trauma centers. (17th February 2016) - Lyon, Regan; Berry-Cabán, Cristóbal S.; Lyon, Christopher; Markowski, Helen; Boltinhouse, Sara L.
ABSTRACT: Objective: Outcomes from previous studies report the driving under the influence (DUI) conviction rates for trauma patients in several cities within Canada and the United States over the last 2 decades. This study reports charge, conviction, and prosecution rates for trauma patients at 2 level I trauma centers servicing a large metropolitan city. Methods: A retrospective review of the trauma databases was completed to identify patients meeting inclusion criteria. Four hundred sixty patients were identified and their records were compared with the district attorney's records for DUI charges and convictions. Results: The conviction rate for this study was 8.7%, demonstrating continued low rates of conviction despite growing interest and public awareness of drinking and driving. Conclusions: We discuss legal considerations that providers should consider when treating patients who have been drinking and driving.